State estimation for neural networks with time-varying delays in the leakage terms. (2018) - Jiang, Chong; Zou, Dexin
The paper is concerned with state estimation for neural networks with time-varying delay in the leakage terms. By constructing an appropriate Lyapunov-Krasovskii functional with double integral terms, and using free-weighting matrix technique and Jensen's inequality approach, new globally asymptotic stability criteria are established. The stability criteria depend on the upper bounds of the transmission discrete time-varying delay, leakage delay as well as their derivation. The presented results can be efficiently solved by resorting to Matlab LMI Toolbox. An example is included to show the effectiveness of the proposed criteria.